2017
DOI: 10.1111/bjh.14866
|View full text |Cite
|
Sign up to set email alerts
|

Activity of lenalidomide in mantle cell lymphoma can be explained by NK cell‐mediated cytotoxicity

Abstract: Lenalidomide is an immunomodulatory agent that has demonstrated clinical benefit for patients with relapsed or refractory mantle cell lymphoma (MCL); however, despite this observed clinical activity, the mechanism of action (MOA) of lenalidomide has not been characterized in this setting. We investigated the MOA of lenalidomide in clinical samples from patients enrolled in the CC-5013-MCL-002 trial (NCT00875667) comparing single-agent lenalidomide versus investigator's choice single-agent therapy and validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 53 publications
0
42
0
Order By: Relevance
“…These results support recent findings from two clinical studies. One study noted early T‐cell activation in patients with relapsed FL or DLBCL in response to lenalidomide monotherapy (Menard et al , ), and another revealed lenalidomide‐mediated enhancement of NK cell proliferation in patients with MCL (Hagner et al , ). Results of our analysis of patient samples from the phase 3 RELEVANCE trial (Morschhauser et al , ) are consistent with those from a phase 2 trial of R 2 in FL, where increased numbers of memory T cells, NK cells, and other immune cell populations were detected in peripheral blood of patients, starting from cycle 2 day 1 of therapy (Fowler et al , ; Morschhauser et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results support recent findings from two clinical studies. One study noted early T‐cell activation in patients with relapsed FL or DLBCL in response to lenalidomide monotherapy (Menard et al , ), and another revealed lenalidomide‐mediated enhancement of NK cell proliferation in patients with MCL (Hagner et al , ). Results of our analysis of patient samples from the phase 3 RELEVANCE trial (Morschhauser et al , ) are consistent with those from a phase 2 trial of R 2 in FL, where increased numbers of memory T cells, NK cells, and other immune cell populations were detected in peripheral blood of patients, starting from cycle 2 day 1 of therapy (Fowler et al , ; Morschhauser et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In neoplastic B cells, degradation of these substrates causes apoptosis, whereas in T cells the result is enhanced co-stimulation signalling and increased interleukin 2 (IL2) production (Gandhi et al, 2014). As a single agent, lenalidomide restores the ability of tumourinfiltrating T cells from patients with B-cell lymphoma to form functional immune synapses with autologous malignant B cells (Ramsay et al, 2008(Ramsay et al, , 2009Hagner et al, 2017). Lenalidomide in combination with rituximab (R 2 ) has been shown to enhance activation of healthy donor NK cells and increase ADCC of various NHL cell lines (Wu et al, 2008;Zhang et al, 2009;Lagrue et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given that a benefit in progression‐free survival (PFS) was observed in the lenalidomide arm, this would seem to be a fitting setting to evaluate its mode of action. Fortunately, cell material from a number of participating patients was available, and in a paper in this issue (Hagner et al , ) several of the above mentioned mechanisms of action are addressed in a longitudinal fashion.…”
mentioning
confidence: 99%
“…Notably, the effect could be shown as significant increases in the number of circulating CD56 + NK cells in responders, but not in non‐responders (with a trend towards increased PFS and overall survival). In addition, in an in vitro setting analysing NK cytotoxicity of MCL cell lines, lenalidomide was shown to act primarily by enhancing the NK synapse formation and secretion of granzyme B (Hagner et al , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation